Ultrasound-guided aspiration of dominant follicles (≥25 mm) followed by luteinization and progesterone production during the estrous cycle in mares - Ignácio, F. S. [UNESP]; Montechiesi, D. F. [UNESP]; Bergfelt, D. R.; Orlandi, C. M.B. [UNESP]; Carvalho, L. R. [UNESP]; Puoli Filho, N. J. [UNESP]; Meira, C. [UNESP] (Elsevier, 2021)
The present study was designed to evaluate luteinization rates subsequent to aspiration of dominant follicles (≥25 mm) in the absence of a functional CL (progesterone <1 ng/mL) and characterize the temporal changes in plasma concentrations of progesterone following aspiration-induced luteinization during the estrous cycle in mares. A total of 29 estrous cycles involving 15 mares in a cross-over design were randomly assigned to five groups: 1) ASP-F≥25 mm (n = 6; follicle aspiration 25–29 mm), 2) ASP-F≥30 mm (n = 6; follicle aspiration 30–34 mm), 3) ASP-F≥35 mm (n = 6; follicle aspiration 35–40 mm), 4) ASP-F≥40 (n = 6; follicle aspiration ≥40), and 5) Control (n = 5; spontaneous ovulation or no follicle aspiration). Subsequent to ovulation (Day 0), PGF was administered to all groups on Day 5, blood samples were collected daily and aspiration of the dominant follicle was done using ultrasound-guided transvaginal follicle needle puncture. Among the follicle aspirations groups 25–29, 30–34, 35–39, and ≥40 mm, the luteinization rates were not different (P > 0.05) at 83, 67, 83, and 100%, respectively. Correspondingly, progesterone concentrations increased (>2 ng/mL) by approximately 6, 7, 5, and 4 d after aspiration, respectively, which were delayed (P < 0.05) in the 25–29 and 30–34 mm follicle aspiration groups compared to 2 d after ovulation in the control group. Thereafter, progesterone reached maximal concentrations (10–11 ng/mL) as averaged over all aspiration groups but were lower (P < 0.05) compared to the mean maximal concentration (18 ng/mL) in the control group. Subsequently, there was a decrease in progesterone concentrations (<2 ng/mL) in response to luteolysis, which was delayed (P < 0.05) in the aspiration groups over Days 16–20 compared to Day 15 in the control group. Despite this discrepancy, the mean length of the interovulatory intervals were not different (P > 0.05) among groups on Day 23. Thus, the present study provided novel information that the luteinization rate is relatively high (83%) and consistent following aspiration of dominant follicles (≥25 mm) in the absence of a functional CL and that the increase in progesterone reaches sustainable progestational concentrations (≥2 ng/mL) in accord with the length of the estrous cycle that may potentially support development and maintenance of early pregnancy in recipient mares involved in an embryo transfer program.
Keywords: Dominant follicles; Follicle aspiration; Luteinization; Mares; Plasma progesterone